2012
DOI: 10.1186/2211-1522-2-4
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress and mental health of Thai caregivers

Abstract: Background As the proportion of elderly people within a population increases there is an accompanying increase in the role of informal caregivers. Many studies on caregivers report negative health outcomes but very few have addressed positive aspects of caregiving. This study examines characteristics of Thai caregivers, the distribution of psychological distress and mental health among caregivers, and the association between caregiver status and psychological distress. Methods This report is based on an ongo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 42 publications
0
13
1
Order By: Relevance
“…was directly affected by their perception of social support, self-esteem and burden. Another study including caregivers to older people in general showed that less contact with colleagues and friends was associated with high psychological distress suggesting that it is important to keep social contacts (Yiengprugsawan et al, 2012). For health care and social services, this indicates the need to identify vulnerable caregivers in order to be able to provide them with support, such as respite care or day care for the person cared for (in our case the PwD) and encourage families to support each other and share the caregiver responsibility.…”
Section: Discussionmentioning
confidence: 99%
“…was directly affected by their perception of social support, self-esteem and burden. Another study including caregivers to older people in general showed that less contact with colleagues and friends was associated with high psychological distress suggesting that it is important to keep social contacts (Yiengprugsawan et al, 2012). For health care and social services, this indicates the need to identify vulnerable caregivers in order to be able to provide them with support, such as respite care or day care for the person cared for (in our case the PwD) and encourage families to support each other and share the caregiver responsibility.…”
Section: Discussionmentioning
confidence: 99%
“…Study by Yiengprugsawan et al among Thai caregivers identified high level of psychological stress among female caregivers with high work burden, because of managing the patient and other household activities similar to the present study. 10 In contrast to this, study by Gupta et al among caregivers of psychiatric and cancer patients in India showed equal level of stress among male and female caregivers.…”
Section: Discussionmentioning
confidence: 41%
“…Caregivers reported higher psychological distress but higher positive mental health (i.e., self-esteem and content with life), higher positive mental capacity (i.e., coping with crises), and higher positive mental quality (i.e., helping others) [17]. Objective health has an indirect effect on psychological distress, in size comparable to the effect exerted by functional status and subjective health [18].…”
Section: Background To the Studymentioning
confidence: 66%